Sensorless Solar Tracker Optimization on Photovoltaic (PV) - Arizhal Firmansyah; Irna Tri Yuniahastuti; Churnia Sari (Jurnal Teknik Elektro dan Komputer TRIAC, 2024)
The development of renewable energy technology is getting more rapid, one of which is using solar energy through photovoltaic (PV) systems. A solar tracker is a device used to optimize the absorption of sunlight by solar panels by following the sun's movement. However, using sensors on solar trackers often requires quite complicated manufacturing. Therefore, this research aims to design a sensorless solar tracker on a photovoltaic (PV) system. The method in this study is to attach the actuator motor to the solar panel frame and move it automatically using Arduino Uno. Data was collected in real-time within three days using three different power supplies. Data collection started at 09.00 WIB with a solar panel tilt of 45° and went to 15.00 WIB with a solar panel tilt of 135°. The results of measurements using a solar tracker on photovoltaic (PV) obtained an average current of 0.74 amperes (A), an average voltage of 18.7 volts (V), and an average power of 14.4 watts (W).